THE APPLICATION OF MODERN TOOLS OF PREINVESTMENT ANALYSIS - D. D. Kuznetsova; T. M. Rogulenko (Вестник университета)
The stability and financial return on investment projects of the domestic oil industry is influenced by many factors: the dynamics of the key rate of the Central Bank of the Russian Federation, foreign and national currency rates, as well as the political and economic situation of the country on the world stage and the behavior of oil exporting countries and OPEC participants. In addition to financial quantitative indicators, it is important for a potential investor to assess other types of risks, that he may face during the implementation of the investment project. The article deals with the tools of pre-investment analysis, applied by oil refining companies in the analysis of future financial flows from implemented investment projects.